PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS XI IPS SMAN 1 IV NAGARI BAYANG UTARA KABUPATEN PESISIR SELATAN - Annisa Fauzana (Jurnal Edukasi dan Penelitian Matematika, 2022)
The tipe of risearch used is a quas experimental with  a researh desig  using Non-equivalen Posttest Only Control Group Desig. academik year. Samples were taken using the Simple Rndom Sampling technique, so that clas XI IPS 1 was chosen as the experimental class and XI IPS 2 as the control clas. The instrument used is in the form of a final test of the ability to understand mathematicall concepts in the form of essay questions. The data obtained were analyzed by normality test, homogenety test and t tes. Basid on the analisis of the final test, it was obtained  that P-value = 0. Because the P-Value is les than = 0.05, it’s mean that thire is an influenc from the aplication of the Tem Assisted Individualization (TAI) learning model on the abiliity to understan mathematical conceps of students, so that the ability to understand mathematical concepts of students who learn with the Team Asisted Individualization (TAI) learning model is better than the ability to understand mathematicallconcepts of students wh’so learn with the drect’s  learning mode’sl.. Keywordsi– Cooperative, TAI, Mathematicall concepts understanding.